2012
DOI: 10.2174/156800912800673293
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of Interferon-Alpha on Cell Growth and Metastasis in Human Nasopharyngeal Carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is a highly malignant and frequently metastasized tumor, and the prognosis is very poor when distant metastases occur. Recently, immunotherapy is becoming a promising therapeutic approach. Interferon-α (IFN-α) represents the cytokines exhibiting the longest record of use in clinical oncology. In this study, we examined the antitumor effects of IFN-α1b on NPC. The results showed that recombinant human IFN-α1b (hIFN-α1b) suppressed cell growth, induced a G1-phase cell cycle arrest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…As a multifunctional cytokine, IFN-α intervenes in tumour cell proliferation and apoptosis, and has been used in the treatment of various malignancies. A previous study determined that cell growth was inhibited by treatment with recombinant human IFN-α1b in human nasopharyngeal carcinoma ( 15 ). IFN-α markedly inhibits the growth of the pheochromocytoma PC12 line and increases apoptosis ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a multifunctional cytokine, IFN-α intervenes in tumour cell proliferation and apoptosis, and has been used in the treatment of various malignancies. A previous study determined that cell growth was inhibited by treatment with recombinant human IFN-α1b in human nasopharyngeal carcinoma ( 15 ). IFN-α markedly inhibits the growth of the pheochromocytoma PC12 line and increases apoptosis ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data have suggested that the antitumor effects of immunotherapeutic drugs are associated with the cell cycle. A previous study demonstrated that T-cells were arrested in the G1-phase by recombinant human IFN-α1b in human nasopharyngeal carcinoma ( 15 ). Maeda et al ( 14 ) also reported that IFN-α induces cell cycle arrest in the G0/G1 phase in the HuH7 hepatocellular carcinoma cell line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HuIFN-αN3, a type I interferon, is a multisubtype protein (8,9) with antiviral, antiproliferative, and antitumour activity (10). It has been used clinically in the treatment of various cancers for over 30 years (11).…”
Section: Abstract: Antiproliferative Activity; Antitumour Activity; mentioning
confidence: 99%
“…It has dual effects of anti-virus and immune regulation (6,7). Recombinant human interferon alpha 1b (rhIFN a 1b, Hapgen®) is a type of genetic engineering interferon developed in China (8), and rhIFNα1b has been used for the treatment of chronic viral hepatitis B, hand, foot and mouth disease and Epstein-Barr virus (EBV) infection (9)(10)(11). In this study, we investigated the effects of rhIFNα1b and other factors on subsequent wheezing in infants diagnosed with viral pneumonia, wheezy bronchitis, and bronchiolitis.…”
Section: Introductionmentioning
confidence: 99%